Structure of the incidence of older people in a demographic context - Anna Hakman (Kharkiv State Academy of Physical Culture, 2019)
The scientific article is devoted to the study of the incidence of elderly people through the prism of the demographic status of the population of Ukraine during 2010-2019. Purpose: to study the dynamics of aging of the population of Ukraine and determine the incidence of elderly people. Material & Methods: analysis of scientific, methodological, regulatory literature, research of data from the State Statistics of Ukraine, copying from medical records. The study processed 487 medical records of the elderly. Results: according to the State Statistics Service of Ukraine, it was determined that from 2010 to 2019 the proportion of people over working age is 1/6 of the country's population and has some upward trend. In the structure of the incidence of elderly people, diseases of the circulatory system, diseases of the musculoskeletal system and connective tissue, and diseases of the nervous system were most often encountered. Conclusions: in Ukraine, as in most countries of the world, the nation is aging. In connection with the deterioration in the health of the population of Ukraine, as evidenced by the results of screening studies, scientists pay attention to the problem of attracting to motor activity.